The geomorphology of the Basin of Iluh Creek (Batman) - Sunkar, Murat; Tonbul, Saadettin (Istanbul Univ, Fac Letters, Dept Geography, 2012)
This study investigates the geomorphological characteristics of the Basin of Iluh Creek located in the southeastern part of the Diyarbakir Basin. The Basin of Iluh Creek corresponds to a syncline delimited by Raman Mountain on the south and Kira Mountain on the east and north. This basin exhibits the characteristics of a plain as it is not deeply split by streams. This basin, which is known as Tilmis Plain, is also called as Batman Plain. The formation of the Basin of Iluh Creek is in parallel with the formation of Diyarbakir Basin, which also includes that basin. The Basin of Iluh Creek was established after the folding and faulting movements during the Miocene and Pliocene. It has taken the present shape as a result of volcanic activities and erosions during the Quaternary. Located at an average altitude of 650 to 800 meters and closed towards the southeast, the Basin of Iluh Creek is delimited by the Anticline of Raman Mountain on the south. The Raman Mountain, whose southward slopes are cut by the right-lateral Raman Fault, has rich oil fields. This anticline is cut from the center by the NW-SE trending faults, thereby resulting in the formation of the canyon-shaped Maymune Gorge. As this gorge was used by the Batman Stream in the past, it shows the characteristics of a mountain pass. The Kira Mountain, which is located on the east, exhibits the characteristics of a volcanic plateau. Five terraces systems have been found at different altitudes on the Valley of Batman Stream which delimits the Basin of Iluh Creek on the west.
Keywords: Iluh Creek; Tilmis Plain; Diyarbakir Basin; Geomorphology; Raman Mountain; Maymune Gorge